Green synthesis of carbon and cobalt oxide composites by 1–Watt laser sintering for flexible supercapacitors - Duy, Le Thai; Ali, Rana Basit; Sial, Qadeer Akbar; Seo, Hyungtak (Ceramics International, 2023)
Transition metal oxides, as well as multivalent metal oxides like Co3O4, have attracted huge attention for energy-storing materials. Combining Co3O4 with carbon materials is of interest to improve the limited electrical conductivity and electrochemical performance of Co3O4 composites. However, most synthesis methods of those Co3O4 and carbon composites commonly need plenty of chemicals with long calcination and release many harmful byproducts. Thus, our green strategy based on laser sintering to synthesize a carbon-Co3O4 composite from a single source – cobalt acetate – is proposed. With a low-power laser, our method is applicable to making flexible devices. A demonstration of flexible supercapacitor cells formed on a silver-nanowires-coated polyimide substrate is presented. Furthermore, the effects of laser pulse duration and current collector conductance on the device performance are investigated. As tested in Na2SO4 and KOH electrolytes, these cells can deliver specific capacitances of 13.2 F g−1 (at 0.08 A g−1) and 48.2 F g−1 (at 1 A g−1), respectively, with a remarkable cycling behavior of 90% after 3000 cycles. Notably, the usability of our composite with the neutral Na2SO4 electrolyte is worth exploring for eco-friendly energy storage. Altogether, our study shows opportunities to create green composites of carbon and multivalent metal oxides quickly and cost-effectively.
Keywords: Carbon material; Electrical conductivity; Energy; Flexible; Green synthesis; Laser sintering; Metal-oxide; Multivalent metals; Oxide metals; Transition-metal oxides; Carbon; Cobalt oxide; Flexible; Laser sintering; Supercapacitor